Accumulation of ricinoleic acid in developing seeds of castor (Ricinus communis) from India - DUBEY, KAUSHIK K DHAR; YADAV, JOGINDER; UPADHYAYA, KAILASH C; KUMAR, ARUNA (The Indian Journal of Agricultural Sciences, 2020)
Plant oils serve as a major resource of food, feed, as well as raw materials for various industrial applications. Castor bean (Ricinus communis L.) is a plant of Euphorbiaceae family which have high level of ricinoleic acid (over 85%) in its seed. Ricinoleic acid is a hydroxy fatty acid (HFA) which is accumulated in seeds as Triacylglycerols (TAGs). Castor oil has a very high demand all over the world and India is the country who majorly fulfils world’s demand. Due to its wide industrial usages and associated undesirable characters such as low genetic variability, presence of toxin ricin and allergens, various approaches such as conventional and transgenic approaches are being undertaken for production of ricinoleic acid. For later, understanding of genes involved in the metabolic pathways for the synthesis and accumulation of such fatty acids are crucial, so that they can be engineered to alternate oilseed crops. Present research work deals with the cloning of fatty acid hydroxylase gene from high oil yielding varieties of castor. This study majorly discussed the accumulation of major fatty acids in developing seeds of castor variety (48-1) which describes storage reserve accumulation. Ricinoleic acid accumulation started between 20-30 days after flowering (DAF) and continued to increase till 40 DAF with a slight decrease during maturation stage. This study can be further utilized for biotechnological interventions for production of ricinoleic acid.